Efficiency and saftety of sodium-glucose cotransporter-2 inhibitors in patients with type 2 diabetes - Nguyen, Xuân Tiến (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Diabetes is a chronic, metabolic disease characterized by elevated levels of blood glucose. Diabetes can lead over time to serious damage to the hearts, blood vessels, eyes, kidneys and nerves in untreated patients with diabetes. The prevalence of diabetes has been steadily increasing, the majority living in low-and middle-income countries. SGLT2i (Sodium Glucose cotransporter 2 inhibitor- SGLT2i) lower blood sugar by causing kidneys to remove sugar from the body through urine. FDA (U.S. Food and Drug Administration) approval for SGLT2i including: canagliflozin, dapagliflozin, empagliflozin, and ertugliflozin. Compared with placebo SGLT2i reduces glycated hemoglobin by 0.5%–1.0% when used as monotherapy or in combination. SGLT2i reduces the risk of Major adverse cardiovascular events (MACE), heart and kidney protection. In addition, SGLT2i induce weight loss 2-3 kg, a low risk of hypoglycemia, and a reduction in blood pressure of about 4 mmHg systolic and 2 mmHg diastolic. Adverse effects of SGLT2i include urinary tract infections, genitourinary infections, and ketoacidosis. Concerns have also been raised about the association of SGLT2i with Fournier gangrene, lower limb amputations, risk of bone fractures, and acute kidney injury.